THE INFLUENCE OF WORD OF MOUTH AND SOCIAL MEDIA ON PATIENTS' INTENTION TO VISIT, MEDIATED BY TRUST: A STUDY OF MEDICAL CHECK-UP SERVICES AT XYZ HOSPITAL SEMARANG - Wynona Ramli; Rudy Pramono (LPSDI Bina Patria, 2025)
Globalization and the expansion of free trade have affected hospitals in Indonesia. In the digital era, hospitals face intense competition, especially in preventive services such as medical check-ups (MCUs). Word of mouth (WOM) and social media have become the main communication tools influencing patient decisions. However, patient trust in hospitals plays an important role as a mediator of the influence of WOM and social media on visit interest. This research analyzes the influence of WOM and social media on patient interest, with trust as a mediating variable. Data show a trend of increasing interest in MCU services after the COVID-19 pandemic. The research results are expected to contribute to marketing communication strategies for healthcare services based on trust and digital engagement. The purpose of this research is to determine the influence of WOM and social media on interest in visiting the MCU service at XYZ Hospital Semarang, with trust as a mediating factor. This is an explanatory quantitative study using a survey design. The sampling technique in this research uses purposive sampling with at least 129 respondents who meet the research criteria. Data were processed using the Partial Least Squares (PLS) method. The research results show that WOM, social media, and trust significantly influence patients’ visit interest; WOM and social media significantly influence trust. Trust significantly mediates the influence of WOM on patients’ visit interest, and trust significantly mediates the influence of social media on patients’ visit interest.